Nitrogen, phosphorus and potassium balance in agriculture of Latin America and the Caribbean - Guareschi, Roni Fernandes Guareschi; Boddey, R.M, Robert Michael Boddey; Alves, B.J.R, Bruno José Rodrigues Alves; Sarkis, L.F, Leonardo Fernandes Sarkis; Martins, M.R, Marcio dos Reis Martins; Jantalia, C.P., Cláudia Pozzi Jantalia; Cabriales, Juan José Peña; Núñez, José Antonio Vera; Urquiaga, S., Segundo Sacramento U Caballero (REVISTA TERRA LATINOAMERICANA, 2019)
The objective of this study was to evaluate nutrient consumption and exports in agricultural systems of Latin America and the Caribbean (ALC) in order to estimate the balance of the main macronutrients (N, P and K) used by crops. The nutrient balance was estimated by considering the amount of nutrients entering the agricultural systems via fertilization and biological N2 f ixation (BNF) and the amount of nutrients leaving the systems through crop harvest removal in each country. Based on off icial statistics for the year 2016, the ALC region presented a positive balance of nitrogen. However, some countries (Argentina, Bolivia and Paraguay) had a negative balance of N. Biological N2 f ixation is the main source of N in Latin American agriculture, accounting for more than 62% (11.29 Mt N) of the total N (18.10 Mt N) entering the agricultural systems. Broadly speaking, the supply of P via fertilizer in Latin America counterbalanced the removal through crop harvest, with the exception of Argentina, Bolivia, Guatemala and México, which have crop production dependent on soil P mining. Potassium was one of the nutrients whose application does not meet the demand of the region’s crops, presenting negative balances in almost all countries except Brazil, Colombia and Venezuela. Nevertheless, it should be noted that many agricultural soils from this region have naturally high K availability. Greater care in the use of inputs, including fertilizers, occurs with cropping soybean, corn, coffee, sugarcane and oranges, while the rest are dependent on natural soil fertility, which may compromise food safety.